Engineered IgG1‐Fc – one fragment to bind them all. Issue 1 (March 2016) - Lobner, Elisabeth; Traxlmayr, Michael W.; Obinger, Christian; Hasenhindl, Christoph
Summary: The crystallizable fragment (Fc) of the immunoglobulin class G (IgG) is a very attractive scaffold for the design of novel therapeutics due to its quality of uniting all essential antibody functions. This article reviews the functionalization of this homodimeric glycoprotein by diversification of structural loops of CH3 domains for the design of Fcabs, i.e. antigen‐binding Fc proteins. It reports the design of libraries for the selection of nanomolar binders with wildtype‐like in vivo half‐life and correlation of Fc receptor binding and ADCC. The in vitro and preclinical biological activity of selected Fcabs is compared with that of clinically approved antibodies. Recently, the great potential of the scaffold for the development of therapeutics for clinical use has been shown when the HER2‐binding Fcab FS102 entered clinical phase I. Furthermore, methods for the engineering of biophysical properties of Fcabs applicable to proteins in general are presented as well as the different approaches in the design of heterodimeric Fc‐based scaffolds used in the generation of bispecific monoclonal antibodies. Finally, this work critically analyzes and compares the various efforts in the design of highly diverse and functional libraries that have been made in the engineering of IgG1‐Fc and structurally similar scaffolds.